Gonadotropin Releasing Hormone Agonists Combined with Hormone Replacement Therapy Significantly Improves Reproductive Outcomes for Patients with Thin Endometrium and Intramural Fibroids in Frozen Embryo Transfer Cycles - Wei L; Tian B; Wang S; Xu S; Zhang C (Drug Design, Development and Therapy)
Longlong Wei,1,2 Bing Tian,2 Shuna Wang,2 Siyue Xu,2 Cuilian Zhang1,2 1People’s Hospital of Zhengzhou University, Zhengzhou, Henan, 45003, People’s Republic of China; 2Department of Reproductive Medicine Center, Henan Provincial People’s Hospital, Zhengzhou, Henan, 45003, People’s Republic of ChinaCorrespondence: Cuilian Zhang, People’s Hospital of Zhengzhou University, No. 7, Wei Wu Road, Zhengzhou City, Henan Province, 450003, People’s Republic of China, Email luckyzcl@qq.comBackground: Both intramural myomas and thin endometrium exert a detrimental influence on the outcomes of assisted reproductive technology (ART). The downregulation of gonadotropin releasing hormone agonists (GnRH-a) is regarded as an effective approach to reducing the size of intramural fibroids and enhancing endometrial receptivity. Consequently, we conducted this study to assess whether the GnRH-a combined with hormone replacement therapy (GnRH-a-HRT) can improve reproductive outcomes in frozen embryo transfer cycles for patients with a thin endometrium (≤ 7 mm) and intramural fibroids.Methods: This retrospective cohort study encompassed 360 patients who underwent frozen embryo transfer following in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles. Patients were stratified into three groups based on the endometrial preparation protocol: the natural cycle (NC) group (n=96), the hormone replacement therapy (HRT) group (n=180), and the GnRH-a-HRT group (n=84). The live birth rate (LBR) was designated as the primary outcome, while clinical pregnancy rate (CPR), miscarriage rate, and ectopic pregnancy rate were classified as secondary outcomes.Results: The LBR and CPR in the GnRH-a-HRT group were significantly higher than those in both the HRT group and the NC group (both P < 0.0001). A logistic regression model indicated that the LBR was significantly higher in the GnRH-a-HRT group compared to both the HRT group (odds ratio, 0.269; 95% confidence interval, 0.114– 0.637; P = 0.003) and the NC group (odds ratio, 0.524; 95% confidence interval, 0.457– 0.956; P = 0.023). Subgroup analyses based on the number and dimension of fibroids demonstrate the positive efficacy of the GnRH-a–HRT regimen.Conclusion: Compared to NC and HRT protocol, improved reproductive outcomes were observed in the GnRH-a–HRT group. These findings provide valuable insights for exploration of the underlying mechanisms by which the GnRH-a-HRT protocol enhances reproductive outcomes in patients of thin endometrium with intramural fibroids.Keywords: frozen embryo transfer, live birth rate, clinical pregnancy rate, thin endometrium, intramural fibroid